A Randomized Control Trial of Cognitive Compensatory Training (CCT) and Computerized Interactive Remediation of Cognition-Training for Schizophrenia (CIRCuiTS) - Dark, Frances Louise; Gore-Jones, Victoria; Newman, Ellie; Wheeler, Maddison; Demonte, Veronica; Northwood, Korinne (Frontiers in Psychiatry, 2022)
Background Various modes of delivering cognitive remediation (CR) are effective, but there have been few head-to-head trials of different approaches. This trial aimed to evaluate the relative effectiveness of two different programmes, Cognitive Compensatory Training (CCT) and Computerized Interactive Remediation of Cognition—Training for Schizophrenia (CIRCuiTs). Methods The study used a single-blind randomized, controlled trial to examine the efficacy and effectiveness of the two therapies. The study aimed to enroll 100 clinically stable patients between the ages of 18 and 65 years who had been diagnosed with a schizophrenia spectrum disorder. Participants were randomized to either the CCT or CIRCuiTs therapy groups. The primary outcome measures were neurocognition using the Brief Assessment of Cognition Scale (BACS) and the Subjective Scale to Investigate Cognition in Schizophrenia (SSTICS). The secondary measure was functional outcomes using the Social Functioning Scale (SFS). Results There was no group difference in any of the outcome measures post-intervention or at follow-up. Both groups had a small improvement on their SSTICS scores between baseline (M = 30.52 and SD = 14.61) and post-intervention (M = 23.96 and SD = 10.92). Verbal memory scores as measured by list learning improved for both groups between baseline (z = −1.62) and 3-month follow-up (z = −1.03). Both groups improved on the token motor task between baseline (z = −1.38) and post-intervention (z = −0.69). Both groups had a decline in Symbol Coding scores between baseline (z = 0.05) and 3-month follow-up (z = −0.82). Discussion This underpowered study found no difference in effect between the two approaches studied. If future studies confirm this finding, then it has implications for services where cost and lack of computer technology could pose a barrier in addressing the cognitive domain of schizophrenia spectrum disorders. The final sample size compromised the power of the study to conclusively determine a significant effect.